Sztálint köszöntjük : magyar költők versei a 70 éves Sztálinhoz. ([Budapest] : Franklin Könyvkiadó Nemzeti Vállalat, 1949)
Poems of Devecseri Gábor, Keszthelyi Zoltán, F. Nagy László, Juhász Ferenc, Képes Géza, Gellért Oszkár, Madarász Emil, Zelk Zoltán, Illyés Gyula, Gábor Andor, Hajnal Anna, Kónya Lajos, Lukács Imre, Földeák János, Gereblyés László, Kuczka Péter, Hegedűs Géza, Szüdi György, Vészi Endre, Mátyás Ferenc, Ladányi László, Aczél Tamás, Somlyó György, Darázs Endre.
HU OSA 300 - RFE/RL collection
Keywords: Stalin, Joseph, -- 1879-1953.; Hungarian poetry -- 20th century